Pengaruh Tata Kelola Perusahaan terhadap Kinerja Perusahaan - Calvina Calvina; Elisabeth Tri Aryanti Istimawani (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this study is to obtain empirical evidence and to test the factors that affect company performance in Indonesia, by using institutional ownership, board size, audit type, firm size, audit committee, board structure, and managerial ownership variables. The firm performance is measured by using Tobin’s Q. Population of this study is the non-financial companies listed in Indonesia Stock Exchange (IDX) during 2014 to 2016. The sample is obtained by using purposive sampling method. There are 376 samples selected as the final samples. Hypotheses tested by using multiple regression analysis. The results of this studies indicates that institutional ownership, board size, audit type, firm size, and managerial ownership shows impact to company performance in Indonesia. But audit committee, and board structure do not have impact on company performance in Indonesia.